Impact of Body Mass Index on Static Postural Control in Adults With and Without Diabetes: A Cross-Sectional Study - Yin, Lianhua; Qin, Jiawei; Chen, Yannan; Xie, Jinjin; Hong, Cuiping; Huang, Jia; Xu, Ying; Liu, Zhizhen; Tao, Jing (Frontiers in Endocrinology, 2021)
Aim The objective of this research was to determine the static postural control differences measured from a force platform in Type 2 diabetes mellitus (T2DM) and healthy control groups with different levels of body mass index (BMI), and detect the static postural control difference between T2DM and healthy control groups stratified by different BMI category. This research also explored the relationship of BMI and static postural performance. Methods We recruited 706 participants with T2DM and 692 healthy controls who were sufficiently matched for age, gender, and BMI in this cross-sectional study. The participants were stratified into three groups by BMI: normal weight, overweight, and obesity. All participants performed two-legged static stance postural control assessment on a firm force platform. The Center of Pressure (CoP) parameters were collected under eyes-open and eyes-closed conditions. Mann–Whitney U test was used to compare the static postural control parameters within each BMI category in both groups. The static postural control parameters among different weight groups were compared by Kruskal–Wallis test, post hoc pair-wise comparison were conducted. Generalized linear model was conducted to examine the association between BMI and static postural control parameters while controlling for confounding factors. Results Healthy control group had statistical difference in most CoP parameters compared to T2DM group based on all BMI categories. Normal weight participants presented significant difference compared with overweight and/or obesity for total track length (TTL) and velocity of CoP displacements in Y direction (V-Y) under eyes-open condition, and for most CoP parameters under eyes-closed condition in both groups. There were statistically significant correlations between BMI and most static postural control parameters under only eyes-closed condition according to the result of generalized linear model. Conclusion T2DM patients had impaired static postural control performance compared to healthy controls at all BMI categories. The findings also indicated the association between BMI and static postural control, where higher BMI individuals showed more static postural instability in both T2DM and healthy controls.